Risk factors for severe dysmenorrhea in Arab women: A focus on war displacement and mental health outcomes - Omar Gammoh; Osama Abo Al Rob; Abdelrahim Alqudah; Ahmed Al-Smadi; Mohamad Obada Dobain; Reham Zeghoul; Alaa A. A. Aljabali; Mervat Alsous (AIMS Press, 2024)
Background: Dysmenorrhea is wide spread gynecological disorder among that affect the quality of life of women world wide. The current study aims to examine whether war displacement, mental health symptoms, and other clinical factors are associated with dysmenorrhea severity. Methods: This is a cross-sectional case-control study recruiting two groups: displaced Syrian women and un-displaced local Jordanian women. Demographics and clinical details were recorded. The severity of dysmenorrhea was assessed using WaLIDD scale, the PHQ-9 scale was emplyed to assess depressive symptoms, anxiety was assessed using the GAD-7 scale, and insomnia was assessed using the ISI-A scale. Predictors of severe dysmenorrhea in females using multivariate binary logistic regression. Results: Out of 808 of the total participants, 396 (49%) were Syrian displaced war refugees, 424 (42.5%) reported using paracetamol, 232 (23.2%) were using NSAIDs, and 257 (25.9%) using herbal remedies. Severe dysmenorrhea was associated with war displacement (OR = 2.14, 95% CI = 1.49-3.08, p < 0.001), not using NSAIDs (OR = 2.75, 95% CI = 1.91-3.95, p < 0.001), not using herbal remedies (OR = 2.01, 95% CI = 1.13-3.60, p = 0.01), depression (OR = 2.14, 95% CI = 1.40-3.29, p < 0.001), and insomnia (OR = 1.66, 95% CI = 1.14-2.42, p = 0.009). Conclusions: War displacement, type of analgesic, depression, and insomnia are risk factors for severe dysmenorrhea.